Assessing Knowledge, Attitudes, and Practices of Augmented Reality Technology in Dentistry: A Cross-Sectional Survey - Ritik Kashwani; Kanika Nirankari; Jyoti Kasana; Priyanka Choudhary; Khushi Ranwa (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: Augmented Reality (AR) technology is increasingly recognized for its potential to enhance various aspects of dental practice, including treatment planning, patient education, and training. Despite this potential, the understanding of dental professionals' knowledge, attitudes, and practices regarding AR technology remains underexplored. The objective of this research is to examine the experience, perceived advantages, and real application of augmented reality (AR) Technologies of dental faculty and students. Methodology: A sample of 132 dental students, some integrated into the workforce as part-time private dentists, and faculty members of a single dental school, completed a self-administered online survey. Knowledge and application of AR technology in dentistry, and Experience with AR practice, were the constructs of the study. An administered questionnaire, partially digital and partially paper and pencil, was divided into two parts: Knowledge Assessment and Practice Assessment. The survey results were analyzed using reference statistics. Results: Knowledge Assessment respondents confirmed understanding Augmented Reality (AR) technology (69.7), and AR technology in dental training/education was recognized (65.9). 57.6% of the participants in the Practice Assessment declared absence of AR in their educational and/or professional practice, but an AR technology practice was wanted (67.4). The self-rated proficiencies that 44.47% of the respondents professed were in the range of self-score 3 in the application of AR (moderate). A small fraction (16.7) declared their AR application self-score was above the higher order. Conclusion: It can be concluded from this work that AR technology in academic and practical dentistry is vastly underutilized, notwithstanding the high realization and appreciation for its application.